The Effect of Solids Residence Time on Chemical Phosphorus Removal in Low Concentration Applications. (1st November 2016) - Conidi, Daniela; Parker, Wayne J.
ABSTRACT: : The effect of solids residence time (SRT) on steady state phosphorus (P) removal when striving for ultralow concentrations through metal salt addition was studied. Lab‐scale continuous flow sequencing batch reactors (SBRs) were operated under high (6.4 mg P/L; 1.4 mol Fe/mol P) and low (3.4 mg P/L; 2.6 mol Fe/mol P) influent phosphate concentrations to characterize P removal. Residual P concentrations, particle size distribution, and microscopy analyses were determined over a range of SRTs. A majority of P removal (94% with 3.4 mg P/L; 83% with 6.4 mg P/L) occurred immediately after iron (Fe) addition with additional removal in the SBRs (3.3–4.8% with 3.4 mg P/L; 5.5–8.8% with 6.4 mg P/L). Soluble P uptake was higher for SRTs ≤ 7.4 days with 3.4 mg P/L and ≤ 14.3 days with 6.4 mg P/L. Normalized P uptake (μg P/mg total suspended solids [TSS]) decreased with SRT providing evidence that aging changed floc properties relevant to P removal. Floc size was found to have no distinguishable influence on P removal. However, changes in floc morphology were consistent with P removal trends.